Helpekksdjfkfodldkdkdodidididisj Help
![Helpekksdjfkfodldkdkdodidididisj Help class=](https://us-static.z-dn.net/files/d60/f7b6db91bd9b10dc1510c84217203516.png)
Answer:
The answers to your questions are given below.
Step-by-step explanation:
1. m∠1 and m∠2 are complementary. This statement was given from the question.
2. m∠1 + m∠2 = 90°. Complementary angles add up to give 90°.
3. m∠2 = 74°. This was given in the question.
4. m∠1 + 74 = 90°. Since m∠1 and m∠2 are complementary. Their sum will add up to give 90°
5. m∠1 = 16°
We can prove m∠1 = 16° as shown below:
m∠1 + m∠2 = 90° (complementary angles)
m∠2 = 74°
m∠1 + 74 = 90°
Collect like terms
m∠1 = 90 – 74
m∠1 = 16°